2022
DOI: 10.3389/fvets.2022.878347
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo Platforms to Study the Primary and Recall Immune Responses to Intracellular Mycobacterial Pathogens and Peptide-Based Vaccines

Abstract: Progress in the study of the immune response to pathogens and candidate vaccines has been impeded by limitations in the methods to study the functional activity of T-cell subsets proliferating in response to antigens processed and presented by antigen presenting cells (APC). As described in this review, during our studies of the bovine immune response to a candidate peptide-based vaccine and candidate rel deletion mutants in Mycobacterium avium paratuberculosis (Map) and Mycbacterium bovis (BCG), we developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…The development of assays to study the primary and recall responses in real time, using the same tissue culture platform, provided an opportunity to begin studies focused on determining how gene products encoded by genes regulated by rel interfere with immune clearance of mycobacterial pathogens. The methods can be used with any species including humans to replicate the studies described in our initial and present report (41).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The development of assays to study the primary and recall responses in real time, using the same tissue culture platform, provided an opportunity to begin studies focused on determining how gene products encoded by genes regulated by rel interfere with immune clearance of mycobacterial pathogens. The methods can be used with any species including humans to replicate the studies described in our initial and present report (41).…”
Section: Discussionmentioning
confidence: 93%
“…The replacement of the chromium release assay and the CFU assay have provided opportunity to study the immune response to mycobacterial pathogens in real time. The methods developed to study the primary and recall responses ex vivo can be used with any species including humans (41). The use of cattle in the present studies has highlighted the value of including a large animal species in the study of mycobacterial pathogens (18, 62).…”
Section: Discussionmentioning
confidence: 99%
“…The development of methods to use cattle as a model species to study the immune response to mycobacterial pathogens has afforded an opportunity to follow up on observations made with a mouse model which showed that deletion of rel abrogates the ability of Mtb to establish a persistent infection (26, 27). Similarly, a Maprel deletion mutant could not establish a persistent infection in cattle or goats (5).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Davis and co-workers developed ex vivo platforms in cattle to study the functional activity of CD4+, CD8+, and γδ T and NK cells stimulated with MAP antigen-primed antigen-presenting cells (dendritic cells (DC) present in the blood, monocyte-derived DC, and monocyte-derived macrophages) [57,[103][104][105]. The authors highlighted the usefulness of these platforms for assessing bacterial viability, the cells' phenotype, cytotoxicity mechanisms and, consequently, for examining the potential role of the cell-mediated immune response in preventing the establishment of a persistent infection of MAP [106].…”
Section: Co-cultures Of Primary Cells Alone or Combined With Cell Linesmentioning
confidence: 99%